Preventive Legal Protection for Children As An Effort to Prevent Economic Exploitation Based on Law Number 35 Of 2014 Concerning Child Protection - tureayu situmeang; Taufiq Ramadhan; Hodriani; Parlaungan Gabriel Siahaan; Dewi Pika Lbn Batu (Jurnal Kewarganegaraan, 2026)
Toba Regency, North Sumatra Province. This phenomenon is triggered by the pressures of poverty, low public legal awareness, and weak oversight of children's rights. This situation demands preventive legal protection to prevent exploitation before it occurs, as mandated by Law Number 35 of 2014 concerning Child Protection. This study aims to analyze the forms of preventive legal protection for children as an effort to prevent economic exploitation in Toba Regency and to identify factors inhibiting its implementation. This study used a normative-empirical method with a qualitative descriptive approach. Primary data were obtained through observation and in-depth interviews with the Toba Regency Women's Empowerment and Child Protection Office (PMDPPA) and the Toba Police. Secondary data were sourced from laws and regulations, books, journals, and scientific literature. Data collection was conducted through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that preventive legal protection for children in Toba Regency has been pursued through outreach, legal education, supervision, and synergy between the local government and law enforcement officials. However, its implementation has not been optimal due to structural, cultural, and social barriers, including family poverty, low legal awareness, and cultural norms that consider children's involvement in economic activities normal.